(untitled) (Jurnal Bahasa, 2020)
Myths created to be metaphors have an element of implicitness, that is, to validate the position of the rulers and the Malay kingdoms as supreme and sovereign states. Such myths also function to validate the origins of the Malay rulers as coming from a noble and honoured lineage. This article analyses the metaphor created by the authors of traditional Malay literature in creating the myth of the powerful character Badang. The analysis was carried out using the Relevance Theory (RT) approach using the Bridging Cross-Reference (BCR) framework and the concept of ad hoc. The data used was obtained from the text of the Sulalat al-Salatin (1997). From a total of 26 data items extracted from the text, three items were used in this analysis. The findings of the study show that the myth of Badangs power is meant to validate the power, sovereignty and recognition given to the lineage of the Malay rulers and the Malay kingdoms. This myth, which is often taken to be one-dimensional, thus clearly contains layers of meaning which can only be discerned through a suitable analysis using the appropriate theory. The analysis shows that the authors of traditional Malay literature possessed great wisdom and were able to convey hidden messages in myths interwoven with history. Keywords: metaphor, Malay kingdoms, myth, Relevance Theory, Sulalat al-Salatin